Economy-Wide Estimates of the Implications of Climate Change: Human Health - Francesco Bosello; Roberto Roson; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2005)
We study the economic impacts of climate-change-induced change in human health, viz. cardiovascular and respiratory disorders, diarrhoea, malaria, dengue fever and schistosomiasis. Changes in morbidity and mortality are interpreted as changes in labour productivity and demand for health care, and used to shock the GTAP-E computable general equilibrium model, calibrated for the year 2050. GDP, welfare and investment fall (rise) in regions with net negative (positive) health impacts. Prices, production, and terms of trade show a mixed pattern. Direct cost estimates, common in climate change impact studies, underestimate the true welfare losses.
Keywords: C68; D58; Q25; 330; Impacts of climate change; Human health; Computable general equilibrium; Klimaveränderung; Gesundheit; Soziale Kosten; Allgemeines Gleichgewicht; Welt; Makroökonomischer Einfluss